A PEMANFAATAN LIMBAH STYROFOAM SEBAGAI BAHAN TAMBAH ASPHALT CONCRETE-WEARING COURSE (AC-WC) DENGAN VARIASI SUHU PENCAMPURAN - Amiruddin; Novia Arinda Filantropie; Shafa Layla Ramadhani; Sri Rezki Artini (PILAR, 2023)
Styrofoam is one of the many wastes that comes from buying electronic equipment or used food containers. The use styrofoam as an additive in the asphalt mixture aims to determine whether the addition of styrofoam can increase the characteristic value of the asphalt mixture, but it can also reduce styrofoam and increase the use value of thestyrofoam. The purpose of this study was to determine the value of the asphalt mixture marshall test with the addition of styrofoam whether it met the requirements and identify the effect of the Asphalt Concrete - Wearing Course (AC-WC) mixture using Styrofoam at various temperatures. This study used styrofoam with levels of 6%, 6.5% and 7% with variations in mixing temperature of 140°C, 150°C, 160°C and 170°C. From the test results and the results of the Marshall characteristic analysis, it was found that the use of temperature variations mixing on styrofoam , namely the higher the mixing temperature, the stability value will increase but with the addition of styrofoam into the asphalt mixture it can cause a decrease in the stability value compared to asphalt mixtures without styrofoam.